Integration and enlargement of the European Union ... : lessons to be drawn for the Arab Region - El-ehwany, naglaa (Cairo University. Faculty of Economics and Politics Science, 2005)
Regional Integration is a process in which neighboring states enter into an agreement in order to upgrade cooperation through common institutions and rules.